Viabilidade agroeconômica de consórcios de cenoura e rúcula em diferentes quantidades de jitirana e arranjos espaciais - Paula, Verícia Fernanda Sales de (Universidade Federal Rural do Semi-Árido, 2011)
Aiming to study the feasibility of carrot and arugula intercrops at different amounts of scarlet starglory incorporated into the soil and spatial arrangements between the component crops, an experiment was conducted on the farm Rafael Fernandes, district of Alagoinha, from November 2010 to February 2011. The experimental design used was randomized complete blocks with the treatments arranged in a 4 x 3 factorial with four replications. The treatments consisted of a combination of four amounts of jitirana incorporated into the soil (7.5, 15.0, 22.5 and 30 t ha-1 on a dry basis) with three spatial arrangements of components crops (2:2, 3:3 and 4:4), which correspond to the rows of carrot alternating with rows of arugula. The characteristics evaluated in carrot were: plant height, number of stems per plant, dry mass of shoots, commercial productivity and productivity classified of roots. In the arugula, the characteristics evaluated were: plant height, number of leaves per plant and yields of green mass and dry mass of shoots. Some indices of efficiency of intercropping systems were used, such as land equivalent ratio (LER), actual yield loss (AYL), intercropping advantage (IA). The economic indicators of gross income, net income, rate of return and profitability index were quantified. The best productive performance of carrot and arugula intercropped was obtained when using the amount of 30 t ha-1 of scarlet starglory incorporated into the soil in the spatial arrangement 2:2. The intercropping of carrot and arugula is agroeconomically feasible with the use of scarlet starglory as green manure
Keywords: Daucus carota; Eruca sativa; Adubação verde; Daucus carota; Eruca sativa; Green manuring; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA